Fermented Cottonseed Meal as a Partial Replacement for Soybean Meal Could Improve the Growth Performance, Immunity and Antioxidant Properties, and Nutrient Digestibility by Altering the Gut Microbiota Profile of Weaned Piglets - Gu, Xueling; Li, Zhiqing; Wang, Jing; Chen, Jiashun; Jiang, Qian; Liu, Nian; Liu, Xiang; Zhang, Fan; Tan, Bie; Li, Hao; Ma, Xiaokang (Frontiers in Microbiology, 2021)
The study investigated the impact of fermented cottonseed meal on growth performance, immunity and antioxidant properties, nutrients digestibility and gut microbiota of weaned piglets, by replacing soybean meal with fermented cottonseed meal in the diet. The experimental piglets were fed with either the soybean meal diet (SBM group) or fermented cottonseed meal diet (FCSM group) for 14 days after weaning. The digestibility of dry matter (DM), organic matter (OM), crude protein (CP), gross energy (GE), amino acids and nitrogen was higher in the FCSM diet than those in the SBM diet (P < 0.05). The piglets in the FCSM group showed greater growth performance and lower diarrhea rate than those in the SBM group (P < 0.05). The concentration of serum immunoglobulin G (IgG) and antioxidase, intestinal and hepatic antioxidase were increased and the concentration of malondialdehyde (MDA) in the serum was decreased in those piglets in the FCSM group comparing to those piglets in the SBM group (P < 0.05). The piglets in the FCSM group had higher concentration of volatile fatty acids (VFAs) in their ileum and cecum and higher Simpson index of ileum than piglets in the SBM group (P < 0.05). The relative abundance of Lactobacillus and [Ruminococcus]_torques_group in ileum and Intestinibacter, norank_f_Muribaculaceae, unclassified_o_Lactobacillales and [Eubacterium]_coprostanoligenes_group in cecum were enhanced in piglets fed with the FCSM diet, whereas the relative abundance of Sarcina and Terrisporobacter were increased in piglets fed with the SBM diet. Overall, FCSM replacing SBM improved the growth performance, immunity and antioxidant properties, nutrient digestibility possibly via the alterant gut microbiota and its metabolism of weaned piglets.